Structural changes in Brazilian industry (1995-2009) - Helena Loiola de Figueiredo; Maria Aparecida Silva Oliveira (CEPAL Review, 2016)
This article analyses the structural changes that took place in Brazilian industry between 1995 and 2009, by considering their intersectoral relations, through input-output analysis using the structural decomposition method and the calculation of linkage indices. The results show that the expansion of final demand plays a key role in industry growth in terms of employment, value added and gross production value. Natural-resource-intensive industry has grown particularly strongly. Another finding is that intersectoral demand has weakened, particularly in scale-intensive sectors that use differentiated technology.